(untitled) (Research, Society and Development, 2023)
The demand for aesthetic procedures is increasing globally, becoming one of the hottest and constantly developing markets in search of effective techniques that meet customer expectations. Minimally invasive procedures are increasingly sought after due to their less invasiveness, reducing adverse effects and possibilities of intercurrences, performance in outpatient settings, fast recovery and lower cost. It is fundamental for professionals to be aware of the aging process and the changes in each tissue layer in order to properly diagnose patients’ complaints and choose the most appropriate treatment technique. This narrative review aims to address the changes caused by aging in the lower third of the face and the most common minimally invasive treatments that can prevent or correct the signs of aging in this area.